Analysis of goals scored in European Championship 2012 - Michailidis, Y.; Michailidis, C.; Primpa, E. (Journal of Human Sport & Exercise, 2013)
The purpose of the present study was to evaluate goal scoring characteristics of European Championship 2012 and the sample consisted of all the games of the final phase of the organization (N=31). The statistical analysis of the results was conducted with the use of the non parametric chi square test. According to the results of the present study the short pass (<10m) was the basic final attacking action in most of the goals (18.4%) when the long pass was at the second place (>10m) (17.1%) and the individual action at third place (14.5%). Most of the goals (40.8%) were scored with shot and then with header (27.6%) and with the inner part of the foot (21.1%). Also the most of the goals achieved through the penalty box (71.1%) (p<0.001). Finally when a team scored the first goal was the winner of the match (70.97%). The findings indicate to the coaches to use a lot of offensive exercises with short and long passes. Also the most of exercises have to locate inside the penalty box. As concerns the impact of the first goal was strong for the match outcome, so the teams have to be prepared to deal with a situation that the opponent scored the first goal.